Efektifitas Pembelajaran Tutor Sebaya Berbantuan Modul Untuk Meningkatkan Komunikasi Matematik Mahasiswa - Adi Candra Kusuma (Cakrawala: Jurnal Pendidikan, 2017)
This type of research is the experiment (quantitative). Various obstacles in the process of learning mathematics has been experienced by the students and teachers themselves in the learning process of mathematics and thus require learning method is suitable. This study aims to know the effectiveness of peer-assisted learning modules to improve communication mathematical Students on number theory material. The subjects of this study Computer Engineering Polytechnic students DIII Harapan Bersama Tegal First Semester classes A and B of the academic year 2016/2017. Data collection methods using observation, interview, test questions such as the validity, reliability, discrimination power, level of difficulty of the questions. The results of the study as follows: (1) individual mastery fulfill minimum criteria completeness (65), classical completeness 75% the proportion of students already get more than 65 already exceeded 75%; (2) the ability of mathematical communications student peer-assisted learning modules at 81.10 is higher than expository amounted to 67.90; (3) an increased ability for 0,397 students mathematic communication medium category.